Small SSEA-4-positive cells from human ovarian cell cultures: related to embryonic stem cells and germinal lineage? - Virant-Klun, Irma; Stimpfel, Martin; Cvjeticanin, Branko; Vrtacnik-Bokal, Eda; Skutella, Thomas (Journal of ovarian research, 2013)
It has already been found that very small embyronic-like stem cells (VSELs) are present in adult human tissues and organs. The aim of this study was to find if there exists any similar population of cells in cell cultures of reproductive tissues and embryonic stem cells, and if these cells have any relation to pluripotency and germinal lineage.